A giant Brunner gland hamartoma successfully treated by endoscopic excision followed by transanal retrieval: A case report. Issue 14 (9th April 2021) - Maruo, Motonobu; Tahara, Tomomitsu; Inoue, Fumihiro; Kasai, Takeshi; Saito, Natsuko; Aoi, Kazunori; Takeo, Masahiro; Sumimoto, Kimi; Yamashina, Masao; Murata, Miki; Koyabu, Masanori; Wakamatsu, Takahiro; et al.
Abstract: Rationale: Brunner gland hamartoma (BGH) is a rare tumor of the duodenum. Although BGH is a benign tumor, larger lesion with gastrointestinal symptoms requires tumor removal. We report a giant BGH, successfully treated by endoscopic excision followed by transanal retrieval. Patient concerns: A 38-year-old woman complained of severe anemia, tarry stool, and vomiting. Diagnoses: Esophagogastroduodenoscopy (EGD) showed a pedunculated giant submucosal mass at the duodenal bulb. Interventions: We attempted to remove it because the lesion seemed to be responsible for patient's anemia and vomiting. The lesion had clear but bulky stalk. We carefully cut the stalk using needle-knife and IT knife2. We tried to retrieve specimen, but the mass could not pass through the pyloric ring because of its size. Then we tried to obtain the specimen from anus. Polyethylene glycol solution was administered to accelerate rapid excretion. Outcomes: The mass was successfully removed and was histologically confirmed as a giant BGH, measuring 55 mm in size. Lessons: Reports about endoscopic resection of giant BGH are rare. Moreover, our case is the first report of transanal retrieval of resected specimen using polyethylene glycol solution. Endoscopic resection of BGH is less-invasive but can be more challenging if the mass is large. Our case provides useful option for endoscopic treatment of giant BGH.